Adding a polyphenol-rich fiber bundle to food impacts the gastrointestinal microbiome and metabolome in dogs - Fritsch, Dale A.; Jackson, Matthew I.; Wernimont, Susan M.; Feld, Geoffrey K.; Badri, Dayakar V.; Brejda, John J.; Cochrane, Chun-Yen; Gross, Kathy L. (Frontiers in Veterinary Science, 2023)
Pet foods fortified with fermentable fibers are often indicated for dogs with gastrointestinal conditions to improve gut health through the production of beneficial postbiotics by the pet’s microbiome. To evaluate the therapeutic underpinnings of prebiotic fiber enrichment, we compared the fecal microbiome, the fecal metabolome, and the serum metabolome of 39 adult dogs with well managed chronic gastroenteritis/enteritis (CGE) and healthy matched controls. The foods tested included a test food (TF1) containing a novel prebiotic fiber bundle, a control food (CF) lacking the fiber bundle, and a commercially available therapeutic food (TF2) indicated for managing fiber-responsive conditions. In this crossover study, all dogs consumed CF for a 4-week wash-in period, were randomized to either TF1 or TF2 and fed for 4 weeks, were fed CF for a 4-week washout period, and then received the other test food for 4 weeks. Meaningful differences were not observed between the healthy and CGE dogs in response to the prebiotic fiber bundle relative to CF. Both TF1 and TF2 improved stool scores compared to CF. TF1-fed dogs showed reduced body weight and fecal ash content compared to either CF or TF2, while stools of TF2-fed dogs showed higher pH and lower moisture content vs TF1. TF1 consumption also resulted in unique fecal and systemic metabolic signatures compared to CF and TF2. TF1-fed dogs showed suppressed signals of fecal bacterial putrefactive metabolism compared to either CF or TF2 and increased saccharolytic signatures compared to TF2. A functional analysis of fecal tryptophan metabolism indicated reductions in fecal kynurenine and indole pathway metabolites with TF1. Among the three foods, TF1 uniquely increased fecal polyphenols and the resulting postbiotics. Compared to CF, consumption of TF1 largely reduced fecal levels of endocannabinoid-like metabolites and sphingolipids while increasing both fecal and circulating polyunsaturated fatty acid profiles, suggesting that TF1 may have modulated gastrointestinal inflammation and motility. Stools of TF1-fed dogs showed reductions in phospholipid profiles, suggesting fiber-dependent changes to colonic mucosal structure. These findings indicate that the use of a specific prebiotic fiber bundle may be beneficial in healthy dogs and in dogs with CGE.